Analisis Kinerja Pelayanan Publik Pada Unit Pelayanan Terpadu Satu Atap Kota Yogyakarta=Analysis of Performance of Public Service at Unit of One Roof Integrated Services in Yogyakarta City - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT This research aims at knowing performance of service and factors influ-encing the performance of public service at Unit of One Roof Integrated Ser-vices in Yogyakarta City. The method used in this research is qualitative-descriptive. The data source collection is done through interview, docu-ments, and direct observation. The result of the research shows that the per-formance of public service at Unit of One Roof Integrated Service at Yogyakarta City is not yet optimal. This can be seen from the certain indicators such as productivity, quality of service, responsiveness, responsibility, and account-ability. While the factors influencing the performance of public service at Unit of One Roof Integrated Services of Yogyakarta City are leadership, struc-ture, human resources, culture, and facility. Based on analysis and data in-terpretation above, the performance of public service at Unit of One Roof Integrated Services of Yogyakarta City, of course, requires to be improved with the several ways. Firstly, the institute should be strengthened to become the formal or the structural institute in order to the leader has the more au-thority so that he can handle the pi ucess of service solution quickly. Secondly, the laws or regulations, which become the compass of duty implementation, should be re-examined. Thirdly, the institute should have incentive system. Fourthly, the quality of apparatus resources should be improved. And finally, it is important to have the evaluation system of the performance of employees so that the position analysis needs to be implemented at Unit of One Roof Integrated Services of Yogyakarta City.